PENGAWASAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU (STUDI KASUS DI KELOMPOK BERMAIN AQILA MANDITA KABUPATEN SUBANG) - Sahilan, Sahilan; Megawati, Devi; Rahayu, Marlina (STKIP Pesisir Selatan, 2025)
Principal supervision plays a crucial role in ensuring the quality of education in a school. As the leader of the institution, the principal is responsible for ensuring that the entire learning process meets established standards. Through effective supervision, the principal can monitor teacher performance, student discipline, and the overall implementation of the curriculum. Furthermore, effective supervision helps create a conducive learning environment, foster a professional work culture, and encourage improvements in educational quality. Without proper supervision, various administrative and academic issues can be overlooked, ultimately negatively impacting student development. Therefore, principal supervision is a crucial aspect in creating a superior and competitive school. The purpose of this study was to determine how principal supervision at the Aqila Mandita Playgroup in Subang Regency improves teacher professionalism. The research method used was a qualitative approach, case studies, data collection, and observation. In this case, there are still teachers who have not been able to adapt to current developments.